THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP OF SCHOOLS PRINCIPAL AND WORK EFFECTIVENESS OF TEACHERS IN SCHOOLS IN AMPHOE LUMLUKKA UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE 4, PATHUMTHANI - Nontisorn, Nipaporn; Sarnswang, Sudarat; Buasuwan, Prompilai (Journal of Educational Review Faculty of Education in MCU, 2020)
The purposes of this research were 1) to study the transformational leadership of school principal in school in amphoe Lamlukka under the secondary educational Service area office 4, Pathumthani 2) to study work effectiveness of teachers’ performance in educational institutions in amphoe Lamlukka under the secondary educational Service area office 4, Pathumthani 3) to study the relationship between transformational leadership of schools principal and work effectiveness of teachers in schools in Amphoe Lumlukka under the Secondary educational service area office 4, Pathumthani. Is a survey study using 163 questionnaires of administrators and teachers in educational institutions and analyzed by statistical data which are. percentage, mean, standard deviation, and Pearson’s correlation coefficient. The results of the research showed that; 1) The transformational leadership for change of school in educational institutions In general, it is at the high level in all 4 aspects which are Idealized Influence Inspiration Motivation of Intellectual Stimulation And the Individualized Consideration. 2) The effectiveness of teachers’ performance in educational institutions In general, it is at the high level in all 5 areas, namely learning management Setting up student support system Class management Building relationships between schools and communities And personal development 3) the relationship between transformational leadership of schools principal and work effectiveness of teachers in schools in Amphoe Lumlukka under the Secondary educational service area office 4, Pathumthani. was found in the positive correlation at a medium level with statistically significance at the .01 level